2021
DOI: 10.1111/jonm.13498
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐to‐nurse horizontal violence in Chinese hospitals and the protective role of head nurse's caring and nurses' group behaviour on it: A cross‐sectional study

Abstract: Aims This study aimed to analyse the prevalence of nurse‐to‐nurse horizontal violence in Chinese hospitals and examine the effects of head nurse's caring and nurse's group behaviour on horizontal violence. Background Horizontal violence is a serious global problem affecting the nursing profession, but little is known of the issue in Chinese hospitals. Increasing evidence has showed that leadership and group factors are important in facilitating horizontal violence. Whether the head nurse's caring and group beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, no relationship was observed between other demographic variables and horizontal violence or turnover intention, probably because it was completed when the COVID-19 pandemic was at its peak, and all nurses were under extreme pressure. Similarly, another survey had found no relationship between horizontal violence and age, gender and work experience (Peng et al, 2021). However, there was one study detecting higher levels of horizontal violence among HCPs with rotating shifts, age of less than 35, work experience of less than 10 years, and male gender (Ghareeb et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no relationship was observed between other demographic variables and horizontal violence or turnover intention, probably because it was completed when the COVID-19 pandemic was at its peak, and all nurses were under extreme pressure. Similarly, another survey had found no relationship between horizontal violence and age, gender and work experience (Peng et al, 2021). However, there was one study detecting higher levels of horizontal violence among HCPs with rotating shifts, age of less than 35, work experience of less than 10 years, and male gender (Ghareeb et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] argued that to address the issue, it is necessary to study its occurrence in other cultural contexts with relevant antecedents and outcomes. Horizontal hostility, also known as nonphysical intergroup conflict, manifests itself in the nursing profession as both overt and hidden hostile behaviours [ 16 , 17 ]. High nurse turnover, absenteeism, lower-quality patient care, and less productivity are some of the potentially disturbing outcomes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several gaps in the existing literature. Some studies have examined the impact of nurse managers' caring behaviors on the working environment and negative behaviors (e.g., workplace bullying), which have been quantitative surveys with small sample sizes [ 13 , 14 ]. A few studies have used a qualitative design to explore clinical nurses' perception of caring behavior towards nursing managers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%